2010
DOI: 10.1073/pnas.1005940107
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics of the Cav2 channel nano-environments in the mammalian brain

Abstract: Local Ca 2+ signaling occurring within nanometers of voltage-gated Ca 2+ (Cav) channels is crucial for CNS function, yet the molecular composition of Cav channel nano-environments is largely unresolved. Here, we used a proteomic strategy combining knockoutcontrolled multiepitope affinity purifications with high-resolution quantitative MS for comprehensive analysis of the molecular nano-environments of the Cav2 channel family in the whole rodent brain. The analysis shows that Cav2 channels, composed of poreform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
316
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(332 citation statements)
references
References 55 publications
15
316
1
Order By: Relevance
“…When the stargazer mouse was identified to have a mutation in a protein that was a homolog of γ1 (termed stargazin or γ2), it was classified as a neuronal calcium channel γ-subunit (15). However, in the study by Müller et al (6), no interactions with any γ-subunits were found, which agrees with the predominantly held view that these proteins are transmembrane AMPA receptor interacting proteins (16).…”
contrasting
confidence: 36%
See 1 more Smart Citation
“…When the stargazer mouse was identified to have a mutation in a protein that was a homolog of γ1 (termed stargazin or γ2), it was classified as a neuronal calcium channel γ-subunit (15). However, in the study by Müller et al (6), no interactions with any γ-subunits were found, which agrees with the predominantly held view that these proteins are transmembrane AMPA receptor interacting proteins (16).…”
contrasting
confidence: 36%
“…Müller et al (6) are dealing with ion channels that are primarily presynaptic, and this is confirmed by the absence of key PSD proteins from the interactome. In this study, complexes of Ca V 2 channels and associated β-subunits from brain have been isolated using affinity purification steps, and MS has been used to identify the copurified proteins.…”
mentioning
confidence: 86%
“…Regulation of Ca 2+ influx is the best-characterized role for Ca V 1.2, but voltage-gated Ca 2+ channels anchor large macromolecular complexes (19) and could therefore control cellular processes independent of Ca 2+ influx. Indeed, the Ca 2+ channel auxiliary subunit β4 controls epiboly in zebrafish through a Ca 2+ -independent manner (20).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the region of amplification could extend beyond the Ca V itself, if augmented by diffusion-impeding assemblies of associated components. In this regard, it is interesting to note that Ca V subtypes interact with a tremendous variety of proteins in different cellular contexts (52,53). Indeed, the very same molecules that aggregate near Ca V channels to convey downstream signals could also act to restrict diffusion, thereby increasing the gain between Ca 2+ flux and biochemical response.…”
Section: Significancementioning
confidence: 99%